Decay mild solutions of fractional differential hemivariational inequalities - Li, Xiuwen; Liu, Zhenhai; Luo, Ricai (Topological Methods in Nonlinear Analysis, 2022)
The goal of this paper is to consider fractional differential hemivariational inequalities (FDHVIs, for short) in the framework of Banach spaces. Our first aim is to investigate the existence of mild solutions to FDHVIs by means of a fixed point technique avoiding the hypothesis of compactness on the semigroup. The second step of the paper is to study the existence of decay mild solutions to FDHVIs via giving asymptotic behavior of Mittag-Leffler function.